Circumcision: Perspective in a Nigerian teaching hospital - L O Abdur-Rahman; A A Nasir; J O Adeniran (Wolters Kluwer Medknow Publications, 2013)
Background: The practice and pattern of male infants circumcised is influenced by culture, religion and socio-economic classification. The debate about the benefits and risks of circumcision has made a hospital-based practice the most acceptable. Objective: The objective of this study is to evaluate the ages, indications, co-morbidity, types and methods of circumcision, usage and mode of anaesthesia and outcome of male circumcision at a tertiary health centre in Nigeria. Materials and Methods: A retrospective review of male circumcision in a paediatric surgery unit was done from January 2002 to December 2007. The data was analysed using SPSS software version 15. Results: There were 438 boys with age ranged between 6 days and 10 years (median 28 days, mean 53.6 days standard deviation 74.2). Neonatal circumcision (<29 days) was 201 (46%) and 318 (72.6%) of the children were circumcised by the 3 rd month of live. Religion or tradition were the major indicators in 384 (87.7%) patients while phimosis 38 (8.7%), paraphimosis 4 (1%), redundant post circumcision skin 10 (2.3%) and defective prepuce in 2 (0.5%) were other indications. Plastibel™ (PD) was used in 214 (48.9%), classical circumcision 194 (44.2%), guillotine technique (GT) and Gomco™ 10 (2.3%) cases each while 10 (2.3%) had a refashioning/re-excision post previous circumcision. There was an increase in use of PD, drop in the use of GT; and increase in the number of circumcision done over the years. Only 39.7% had anaesthesia administered and complication rate was 6.7%. Conclusion: Neonatal circumcision was highest in the hospital-based circumcision practice, which allowed the expected ideals in the use of devices in a tertiary health centre. However, the low rate of anaesthetic use is unacceptable.